Anxiety and its associated factors among school-going adolescents in Malaysia - Muhd Hafizuddin Taufik Ramli; Muhammad Solihin Rezali; Nik Adilah Shahein; Norhafizah Sahril; Chan, Ying Ying; Nor’ Ain Ab Wahab (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Many mental health disorders have onset during adolescence. To date, the data on the correlates of anxiety is still lacking. Therefore, this study is crucial to determine the factors associated with anxiety among school-going adolescents in Malaysia. Methods This study was based on 26,892 school-going adolescents from 212 selected schools in Malaysia. Anxiety was measured using Depression Anxiety and Stress Scale (DASS-21). Associations between anxiety, sociodemographic characteristics and variables of interest were examined using multivariable logistic regression. Results Overall, 10,540 (39.7%) school-going adolescents had anxiety. Anxiety was positively associated with female (odds ratio, OR [95% confidence interval, CI] = 1.30 [1.19,1.42]) compared to male counterpart, feeling loneliness (1.78 [1.54,2.05]) compared to not lonely, unable to sleep due to worry of something (1.79 [1.56,2.05]) compared to able to sleep, being bullied (1.66 [1.48,1.87]) compared to not being bullied, physical abuse (1.33 [1.18,1.49]) compared to no physical abuse, verbal abuse (1.47 [1.35,1.59]) compared to no verbal abuse, current drinker (1.23 [1.06,1.43]) compared to not current drinker, current drug use (1.84 [1.43,2.35]) compared to not current drug use, ever had sex (1.17 [1.01,1.36]) compared to never had sex, physically inactive (1.16 [1.06,1.26]) compared to physically active and internet addiction (2.59 [2.37,2.83]) compared to no internet addiction. Chinese ethnic (0.68 [0.50,0.93]) compared to other ethnic, and Form 2 (0.78 [0.69,0.89]) and Form 3 (0.73 [0.65,0.82]) students compared to Form 1 students, were protective of anxiety. Conclusions Prevention and intervention programs for these “at-risk” adolescents should be planned holistically towards reducing the risk factors.